Dietary Awareness Level Among Sixth Grade Students A Field Study in the First Cycle of the Basic Education in Lattakia City - أسعد ميرنا; أحلام ياسين; لمى القاضي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the current research is to know the level of dietary awareness among students of the sixth grade in the schools of the first cycle of basic education in the city of Lattakia, and to know the level of dietary awareness among students according to the sex variable. The researcher used the descriptive approach, and in order to achieve the objectives of the research researcher used the Dietary awareness questionnaire, which consisted of (44) items, was applied to a sample of (308) students from the sixth grade in the schools of Lattakia for the academic year 2022/2023. The validity of the questionnaire was verified by presenting it specialized arbitrators. Its constancy was assured by applying it on a pilot sample consisted of (42) students through Cronbach – Alpha Reliability (0.966), and (0.976) at Spearman-Brown. The results of the research showed that the level of dietary awareness among the sixth graders was moderate, and there were differences in the level of dietary awareness according to the gender variable in favor of the female students. In light of the findings of the research, several recommendations were made as follows: holding seminars to raise the level of dietary awareness among students, spreading healthy eating habits among students, introducing health education into the school curricula, conducting a similar study on the level of dietary awareness in different stages of study, And compare its results with the results of the current search.